Thrombocytopenia after second exposure to abciximab is caused by antibodies that recognize abciximab-coated platelets - Curtis, Brian R.; Swyers, Julia; Divgi, Ajit; McFarland, Janice G.; Aster, Richard H. (Blood, 2002)
Thrombocytopenia, often severe, occurs in 1% to 2% of patients given the fibrinogen receptor antagonist abciximab, a chimeric Fab fragment containing murine specificity-determining and human framework sequences. The cause of this complication has not yet been defined. Studies of 9 patients who developed profound thrombocytopenia (platelets <10 × 109/L [10 000/µL]) within a few hours of being given abciximab a second time showed that each had a strong immunoglobulin G (IgG) antibody that recognized platelets sensitized with abciximab. Five patients also had IgM antibodies. IgG antibodies reactive with abciximab-coated platelets were also found in 77 (74%) of 104 healthy subjects. However, the patient antibodies could be distinguished from “normal” ones in 2 ways: (1) only the patient antibodies reacted preferentially with platelets sensitized with the intact monoclonal antibody 7E3 from which the murine sequences in abciximab are derived; and (2) the “normal” antibodies could be inhibited by Fab fragments derived from normal human IgG, whereas the patient antibodies were relatively resistant to this treatment. The findings suggest that antibodies from the patients are specific for murine sequences in abciximab and are capable of causing life-threatening thrombocytopenia upon injection of this drug. The antibodies commonly found in healthy subjects are specific for the papain cleavage site of any Fab fragments and, although they react with abciximab-coated platelets, appear not to cause significant thrombocytopenia. It may be possible to identify patients at risk for developing thrombocytopenia if given abciximab by screening for antibodies that recognize 7E3-coated platelets.